Citizens, Denizens and the Res Publica: Environmental Ethics, Structures of Feeling and Political Expression. (1st May 2005) - Smith, Mick
Environmental ethics should be understood as a radical project that challenges the limits of contemporary ethical and political expression, a limit historically defined by the concept of the citizen. This dominant model of public being, frequently justified in terms of a formal or procedural rationality, facilitates an exclusionary ethos that fails to properly represent our concerns for the non-human world. It tends to regard emotionally mediated concerns for others as a source of irrational and subjective distortions in an otherwise rationally ordered ethico-political community. In doing so it underestimates the important role played by 'structures of feeling', those culturally variable patterns of emotionally mediated responses, that provide the (shifting) grounds for all ethical experience, motivation, communication and interpretation. An alternative model of political expression more suitable to an environmental ethic, the denizen, is suggested.